Uji Efek Toksik Ekstrak Akar Putri Malu (Mimosa pudica L.) terhadap Diameter dan Kerusakan Pulau Langerhans Pankreas pada Mencit (Mus musculus) - La Eddy; Febriyanti Y. Kdise; Amos Killay; Abdul M Ukratalo; Pieter Kakisina (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The root of Mimosa pudica L. contains mimosine, a toxic alkaloid, as well as tannins that exhibit toxic properties, potentially disrupting pancreatic function. Exposure to sufficiently high concentrations of toxic compounds can impair cellular metabolism, leading to irreversible damage. One of the cellular changes induced by cytotoxic compounds is the reduction in the size of pancreatic Langerhans islets. This study aimed to investigate the effects of ethanol extract of Mimosa pudica roots on the diameter of Langerhans islets and β-cell damage in the pancreas of mice. Twelve mice were randomly divided into four groups, each consisting of three animals. Group I served as a control and did not receive the extract, whereas Groups II, III, and IV were administered root extract at doses of 10 mg/g BW, 100 mg/g BW, and 1000 mg/g BW, respectively, for 14 consecutive days. The results demonstrated that administration of ethanol extract of Mimosa pudica roots reduced the diameter of pancreatic Langerhans islets in a dose-dependent manner, with higher doses causing more severe β-cell damage. These findings highlight the need for caution in the use of Mimosa pudica roots as traditional medicine or dietary supplements.